Ethical imperatives for legal educators to promote law student wellbeing. (2nd July 2020) - Duncan, Nigel; Field, Rachael; Strevens, Caroline
ABSTRACT: There is currently a debate about resilience and wellbeing of law students and legal practitioners. Tension has developed between a movement promoting the wellbeing of students and those who criticise that movement for individualising responsibility and enabling managers to evade their responsibilities. This article seeks a constructive resolution of that tension. It proposes ethical obligations for intentional curriculum design for the promotion of student well-being and the ongoing well-being of practitioners. In order to do this it explores different theoretical perspectives on ethical practice. It then uses self-determination theory, a theory of positive psychology, as a basis for applying the outcome of this analysis to the task of educating lawyers. Finally, it considers the implications of these analyses for the continuing responsibilities of the relevant communities: legal educators; practitioners, their employers and managers; regulators; and for the individual law student and lawyer.